ESTIMATION OF MICRONUTRIENTS IN THE SOIL - SHUKLA, GARIMA; SINGH, S. K (The Bioscan, 2016)
In present paper, content of some important major micronutrients namely zinc, boron and iron were estimated at different unsampled locations in Sevapuri block of Varanasi district, Uttar Pradesh by using some Geostatistical techniques. Exponential and spherical semivariograms models were found the best on the basis of the higher values of R2 and lower values of RSS. With the help of these variogram models and interpolating techniques spatial distribution maps of soil micronutrients were prepared and it was found that spatial dependence level of zinc and boron are moderate so they are deficient in the soil of Sevapuri block whereas spatial dependence level of Fe is strong, hence medium and deficient in the soil of Sevapuri block.